Optimization of Extraction Process and Preclinical Evaluation of Marsilea quadrifolia L. in Streptozotocin-Induced Diabetic Rats - Bhanukiran K.; Dubey T.; Hemalatha S. (My University, 2025)
Marsilea quadrifolia is traditionally used for treatment of diabetes by the natives of Jharkhand in India. The current study is focused on optimization of extraction process and validation of traditional claim of the plant Marsilea quadrifolia Lin streptozotocin-nicotinamide induced type2 diabetic rats.Box Behnken Design (BBD) software was used for optimization of extraction process and total phenolic content of the plant. Antidiabetic potential of hydroalcoholic extract (150mg/kg, 300mg/kg, 450mg/kg) was evaluated through in-vivo rat model, and diabetes was induced by an intraperitoneal injection of nicotinamide (110mg/kg, i.p.) followed by streptozotocin injection (65mg/kg, i.p.). Glibenclamide (10mg/kg, per oral) was used as standard drug during treatment. Extractive yield and total phenolic content were found to be 14.1% and 119.45mg/g gallic acid of dried extract, respectively. The hydroalcoholic extract of M. quadrifolia exhibited significant reduction in blood glucose level at a dose of 150mg/kg, 300mg/kg, and 450mg/kg in a dose-dependent manner when compared to standard Glibenclamide (10mg/kg, per oral). Moreover, extract showed improvement in biochemical parameters, such as lipid profile, body weight, liver glycogen, and in-vivo antioxidant potency. Furthermore, histopathological examinations were performed on rat brains. Our work potentially validates the traditional claim of plant being used as anti-diabetic, using STZ induced rat model. The total phenolic content of hydroalcoholic extract of M. quadrifolia L. may be responsible for its anti-diabetic potential. © RJPT All right reserved.